2021
DOI: 10.7759/cureus.14517
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Hyperthyroidism and Ovarian Cytoarchitecture in Albino Rats

Abstract: BackgroundHyperthyroid females often complain of menstrual disturbances and impaired fertility. This study was designed to observe the effect of hyperthyroidism on ovarian folliculogenesis and the hypophyseal-gonadal axis. MethodologyAdult female Wistar albino rats (n= 12), six to eight weeks of age, and weighing 70-162 g, were divided randomly into control (Group A) and experimental (Group B) groups. Group A received daily intraperitoneal injections of 250 µL normal saline (10 µL 5 µM NaOH dissolved in it) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…A number of researchers indicate that any dysfunction of the thyroid gland (both hypothyroidism and hyperthyroidism) affects the reproductive system in mammals. In particular, Liu J et al (2018) found a decrease in the serum GnRH and FSH levels in female rats both in hypothyroidism and hyperthyroidism [27], and Mahmud T et al (2021) showed that adult rats with hyperthyroidism had low levels of estradiol and progesterone, and the amount of FSH and LH either did not change or decreased [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of researchers indicate that any dysfunction of the thyroid gland (both hypothyroidism and hyperthyroidism) affects the reproductive system in mammals. In particular, Liu J et al (2018) found a decrease in the serum GnRH and FSH levels in female rats both in hypothyroidism and hyperthyroidism [27], and Mahmud T et al (2021) showed that adult rats with hyperthyroidism had low levels of estradiol and progesterone, and the amount of FSH and LH either did not change or decreased [12].…”
Section: Discussionmentioning
confidence: 99%
“…The alpha subunit is common with other pituitary hormones, follicle-stimulating hormone (FSH), luteinizing hormone (LH), and human chorionic gonadotropin (HCG), while the beta subunit is specific for TSH and determines an interaction with the TSH receptor [11]. An imbalance between the main regulatory axes leads to pathological reactions by the body [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Meng et al reported reduced preantral and antral follicle counts alongside accelerated follicular atresia in hypothyroid rats, while others noted no difference in follicle counts, despite follicle size differences, in hypothyroid rabbits [ 93 , 94 ]. The effects of excess TH appear to trend in the opposing direction, as Mahmud et al reported reduced ovarian size in hyperthyroid rats with an increase in primordial, primary, and secondary follicles [ 95 ]. The physiological synergy between the actions of THs and FSH may account for diminished ovarian granulosa cell responsiveness to FSH in hypothyroid and hyperthyroid states [ 96 ].…”
Section: Thyroid Hormones and Reproductive Physiologymentioning
confidence: 99%
“…Bu da TH'larının bu dokunun fonksiyonu üzerinde etkili olduğunu göstermektedir. 7 Ayrıca TH'larının karaciğerde seks hormonu bağlayıcı globulin (SHBG) denilen bir glikoproteinin sentezini uyardığı bilinmektedir. Hipertiroidizmde estradiol artışının, estradiolün SHBG'ye artan bağlanmasına ve metabolik klirens hızının azalmasına bağlı olduğu düşünülmektedir.…”
Section: Introductionunclassified